Framing analysis of Bromo fire news in Metro TV editorial review: Pan and Kosicki’s perspective - Khusnul Khotimah; Hengky Fairuz Busthomy (Jurnal CULTURE (Culture, Language, and Literature Review), 2024)
This research aims to explain the framing contained in the Editorial Review Media Indonesia Metro TV program "Expensive Lessons from the Bromo Fire". This research was conducted using framing analysis proposed by Zong Dang Pan and Gerald M. Kosicki. Pan and Kosicki's framing analysis focuses more on dividing news structures into four parts, namely syntactic, script, thematic, and rhetorical structures. The research method used is a qualitative descriptive method, which is carried out by describing data in the form of words. Data was collected through listening and note-taking techniques. The research results show that the editorial analysis of the Metro TV program has fulfilled the entire news structure, starting from syntactic, script, thematic, and rhetorical structures. Based on its syntactic structure, the Metro TV editorial review program chooses to use titles that are concise, clear, and cover the entire content of the news. Based on the structure of the manuscript, the editorial review program meets the 5W+1H principle. If seen from its thematic structure, the editorial review program is divided into seven interrelated parts. Likewise, based on the rhetorical structure, the editorial review program also adds images and videos to support the truth of the information displayed.